Epidemiology, Disease Severity and Outcome of Severe Acute Respiratory Syndrome Coronavirus 2 and Influenza Viruses Coinfection Seen at Egypt Integrated Acute Respiratory Infections Surveillance, 2020–2022 - Fahim, Manal; Roshdy, Wael H.; Deghedy, Ola; Kamel, Reham; Naguib, Amel; Showky, Shymaa; Elguindy, Nancy; Abdel Fattah, Mohammad; Afifi, Salma; Mohsen, Amira; Kandeel, Amr; Abdelghaffar, Khaled (The Canadian journal of infectious diseases & medical microbiology, 2022)
Background. Cocirculation of influenza (Flu) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (SARS-CoV-2/Flu) represent a public health concern as it may worsen the severity and increase fatality from coronavirus disease 2019. An increase in the number of patients with coinfection was recently reported. We studied epidemiology, severity, and outcome of patients with SARS-CoV-2/Flu coinfection seen at Egypt’s integrated acute respiratory infections surveillance to better describe disease impact and guide effective preventive measures. Methods. The first two outpatients were seen daily, and every fifth patient admitted to 19 sentinel hospitals with respiratory symptoms was enrolled. Patients were interviewed using a standardized questionnaire and provided nasopharyngeal swabs to be tested for SARS-CoV-2 and influenza by real-time polymerase chain reaction at the central laboratory. Data from all patients with coinfection were obtained, and descriptive data analysis was performed for patients’ demographics, clinical course, and outcome. Results. The total number of patients enrolled between January 2020 and April 2022 was 18,160 and 6,453 (35.5%) tested positive for viruses, including 52 (0.8%) coinfection. Of them, 36 (69.2%) were coinfected with Flu A/H3, 9 (17.3%) Flu-B, and 7 (13.5%) Flu A/H1. Patients’ mean age was 33.2 ± 21, 55.8% were males, and 20 (38.5%) were hospitalized, with mean hospital days 6.7 ± 6. At the hospital, 14 (70.0%) developed pneumonia, 6 (30.0%) ICU admitted, and 4 (20.0%) died. The hospitalization rate among patients coinfected with Flu-B and Flu A/H3 was 55.6 and 41.7%, with mean hospital days (8.0 ± 6 and 6.4 ± 6), pneumonia infection (40.0 and 80.0%), ICU admission (40.0 and 26.7%), and death (20.0% for both), while no patients hospitalized with A/H1. Conclusions. The recent increase in the number of SARS-CoV-2/Flu coinfections was identified in Egypt. The disease could have a severe course and high fatality, especially in those coinfected with Flu-B and Flu A/H3. Monitoring disease severity and impact is required to guide preventive strategy.